Transfer of meatball and nugget making and nugget making technology as development of merang mushroom processed products in Rambutpuji District, Jember Regency - Niken Widya Palupi; Supiastutik Supiastutik; Subekah Nawa Kartikasari; Eka Ruriani (Future Science, 2019)
IbM's activities on the socialization of making meatballs and nuggets as developers of processed meat-based products are to introduce to the people of Jember, especially those who live in the area of ​​mushroom mushrooms, about the appropriate technology for making meatball and mushroom mushrooms. This IbM activity is carried out at UD. KAOLA MANDIRI located in Rambigundam Village, Rambipuji District, Jember Regency. Mushroom farmers are given training and training on the technology of making mushroom substitution meatballs and mushroom mushroom nuggets. To facilitate understanding of mushroom farmers regarding the technology of making meatballs and nuggets, training activities are carried out by direct practice. The whole participants are mushroom farmers invited to be directly involved in the activities of making products. The technology of making meatballs and nuggets in the utilization of straw mushrooms as substitute or substitute materials can be easily absorbed and the level of enthusiasm of participants in the training material is very high.